2009
DOI: 10.1063/1.3216577
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence from Ge on Si substrate at room temperature

Abstract: A Ge/Si heterojunction light emitting diode with a p+-Ge/i-Ge/N+–Si structure was fabricated using the ultrahigh vacuum chemical vapor deposition technology on N+–Si substrate. The device had a good I-V rectifying behavior. Under forward bias voltage ranging from 1.1 to 2.5 V, electroluminescence around 1565 nm was observed at room temperature. The mechanism of the light emission is discussed by the radiative lifetime and the scattering rate. The results indicate that germanium is a potential candidate for sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…In particular, introducing the Ge Young modulus under biaxial stress Y and defining the x axis oriented along the [1][2][3][4][5][6][7][8][9][10] the solid line is drawn as a reference for the printed version and for the graphs in Fig. 3), the σ RSS maximum position (star), the relative glide plane (blue online; the dashed line is drawn as a reference for the printed version and for the graphs in Fig.…”
Section: Dislocation Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, introducing the Ge Young modulus under biaxial stress Y and defining the x axis oriented along the [1][2][3][4][5][6][7][8][9][10] the solid line is drawn as a reference for the printed version and for the graphs in Fig. 3), the σ RSS maximum position (star), the relative glide plane (blue online; the dashed line is drawn as a reference for the printed version and for the graphs in Fig.…”
Section: Dislocation Modelingmentioning
confidence: 99%
“…Several mechanisms have been proposed to explain the presence and the abundance of edge dislocations in high-misfit SiGe systems. [12][13][14][15] One of the most credited hypotheses concerns an induced nucleation mechanism promoting the nucleation and junction of two 60 • dislocations, usually called complementary dislocations, characterized by having Burgers vectors giving rise to Lomer dislocation if joined (e.g., b 1 = a/2 [1][2][3][4][5][6][7][8][9][10]). 10 In particular, it has been suggested that the stress field of a first dislocation already existing at the interface induces the nucleation of a complementary 60 • dislocation that has as a glide plane the mirrorlike symmetric glide plane of the first, intersecting it exactly at the interface (ML plane in the following).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This successful method led to the realization of light emitting sources [6][7][8] and optically pumped lasers [9] operating at 1:55 m. Similarly, direct-band-gap photoluminescence (PL) was obtained from other tensile-strained n-type Ge structures, where the strain was applied to the material using external mechanical methods [10][11][12][13].…”
mentioning
confidence: 99%
“…1 In addition, theoretical modeling and experimental data demonstrate the feasibility of optical gain and lasing from band-engineered Ge-on-Si. [2][3][4][5][6] The growth of phosphorus doped Ge epitaxial layer on Si is one of the critical steps to implement the devices experimentally. Thus the knowledge on in situ phosphorus diffusion behavior in epitaxial Ge on Si would be great helpful for realization of these devices.…”
mentioning
confidence: 99%